Multicellularity in green algae: upsizing in a walled complex - Domozych, David S.; Domozych, Catherine E. (Frontiers in Plant Science, 2014)
Modern green algae constitute a large and diverse taxonomic assemblage that encompasses many multicellular phenotypes including colonial, filamentous and parenchymatous forms. In all multicellular green algae, each cell is surrounded by an extracellular matrix, most often in the form of a cell wall. Volvocalean taxa like Volvox have an elaborate, gel-like, hydroxyproline rich glycoprotein covering that contains the cells of the colony. In “ulvophytes”, uronic acid-rich and sulfated polysaccharides are the likely adhesion agents that maintain the multicellular habit. Charophytes also produce polysaccharide-rich cell walls and in late divergent taxa, pectin plays a critical role in cell-adhesion in the multicellular complex. Cell walls are products of coordinated interaction of membrane trafficking, cytoskeletal dynamics and the cell’s signal transduction machinery responding both to precise internal clocks and external environmental cues. Most often, these activities must be synchronized with the secretion, deposition and remodeling of the polymers of the extracellular matrix. Rapid advances in molecular genetics, cell biology and cell wall biochemistry of green algae will soon provide new insights into the evolution and subcellular processes leading to multicellularity.